Titanium particle adsorbent and preparation method thereof

By adopting the microwave-ultrasonic compound field synergistic action in titanium-based particle adsorbents, its stability and anti-dissolving performance are improved, the problem of high dissolution rate in the existing technology is solved, and multiple recycling and economic benefits are achieved Improvement.

CN119281286AActive Publication Date: 2025-01-10SICHUAN TAILI XINGKUN NEW MATERIAL CO LTD

Patent Information

Application Number
CN202411411927.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-10
Estimated Expiration
2044-10-10

AI Technical Summary

Technical Problem

The existing titanium-based particle adsorbent has a high dissolution rate during the lithium extraction process of salt lake brine, resulting in structural damage and degradation of performance, which cannot meet the needs of multiple recycling, limiting its wide application in industrial applications.

Method used

Adopt the coordinated action of microwave-ultrasonic composite field, providing uniform heating and internal heating mechanism through microwave, accelerating the cavitation and mechanical stirring of ultrasonic waves, promoting the dispersion and mixing of materials, and improving the stability and anti-soluble properties of titanium-based particle adsorbents. .

Benefits of technology

It has achieved excellent anti-soluble loss performance of titanium-based particle adsorbents, met the needs of multiple recycling, reduced production costs, and improved the economic benefits of lithium extraction in salt lake brine.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119281286A_ABST
    Figure CN119281286A_ABST
Patent Text Reader

Abstract

The invention relates to a titanium particle adsorbent and a preparation method thereof, and relates to the technical field of titanium particle adsorbents, the preparation method of the titanium particle adsorbent comprises the following steps: obtaining a lithium metatitanate precursor; adding the lithium metatitanate precursor, a bonding forming agent and a pore forming agent into a first solvent, and stirring and mixing to obtain a first mixture; the first mixture is placed in a microwave-ultrasonic wave composite field to be subjected to microwave-ultrasonic wave cooperative treatment, and a second mixture is obtained; and granulating the second mixture, acidizing, filtering and drying to obtain the titanium granular adsorbent. On the basis of an existing titanium system particle adsorbent preparation process, the stability of the obtained titanium system particle adsorbent is remarkably improved through the synergistic effect of a microwave-ultrasonic wave composite field, so that the titanium system particle adsorbent has excellent solution loss resistance, and the requirement for repeated recycling in practical application is met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of titanium-based particle adsorbents, and in particular to a titanium-based particle adsorbent and a preparation method thereof. Background Art

[0002] In the context of global energy transformation and rapid development of new energy industries, the demand for lithium resources, as a key raw material for lithium-ion batteries, has shown explosive growth. As one of the important sources of lithium resources, salt lake brine has the advantages of large reserves and relatively low mining costs. Therefore, efficient extraction of lithium from salt lake brine has become a current research hotspot.

[0003] In the technical system of lithium extraction from salt lake brine, the adsorption method is favored due to its simple process, convenient operation, and environmental friendliness. Among them, titanium-based particle adsorbents have shown great application potential in lithium extraction from salt lake brine due to their good chemical stability, high adsorption capacity, and excellent ion selectivity.

[0004] However, existing titanium-based particle adsorbents still have some problems in practical applications, especially the high dissolution rate. Since salt lake brine has a complex composition and contains a variety of corrosive ions and impurities, these ions and impurities are likely to corrode the adsorbent when in contact with it, causing structural damage and performance degradation. Therefore, existing titanium-based particle adsorbents often cannot meet the needs of multiple recycling in practical applications, which not only increases production costs, but also limits their widespread application in lithium extraction from salt lake brine.

[0005] Therefore, granulation technology is particularly important in view of the challenges faced by titanium-based particulate adsorbents in industrial application scenarios. The granulation process can convert the original powder material into particles with a certain shape and size, thereby significantly improving the material's handling performance and ease of operation. Under industrial equipment conditions, powder materials often have problems such as poor fluidity, easy flying, and difficulty in accurately controlling the amount of feed. These problems not only affect production efficiency, but may also pose a threat to workers' health. Through granulation, these problems can be effectively solved, the bulk density and fluidity of the material can be improved, dust pollution can be reduced, and it is convenient for storage, transportation and processing, thereby optimizing the entire production process.

[0006] For titanium-based particle adsorbents, granulation technology can not only improve their physical properties, enhance their stability and durability in industrial applications, but also help improve their ability to resist dissolution and extend their service life, thereby reducing production costs and improving the overall economic benefits of lithium extraction from salt lake brine. Therefore, the development of advanced granulation technology suitable for titanium-based particle adsorbents is of great significance for promoting the industrialization of lithium extraction technology from salt lake brine and realizing the sustainable development and utilization of lithium resources. Summary of the invention

[0007] In order to solve the above problems, the present invention provides a titanium-based particle adsorbent and a preparation method thereof.

[0008] In a first aspect, the present invention provides a method for preparing a titanium-based particle adsorbent, the method for preparing a titanium-based particle adsorbent comprising the following steps:

[0009] Obtaining a lithium metatitanate precursor;

[0010] Adding the lithium metatitanate precursor, the adhesive forming agent and the pore-forming agent into a first solvent and stirring and mixing them to obtain a first mixture;

[0011] placing the first mixed material in a microwave-ultrasonic composite field for microwave-ultrasonic synergistic treatment to obtain a second mixed material;

[0012] Granulating the second mixed material, and then acidifying, filtering and drying to obtain the titanium-based particle adsorbent;

[0013] The working condition parameters of the microwave-ultrasound synergistic treatment include: ultrasonic power of 1500-1800W, and microwave power of 150-220W.

[0014] Furthermore, the ultrasonic power of the microwave-ultrasonic synergistic treatment is 1720-1750W.

[0015] Furthermore, the microwave power of the microwave-ultrasound synergistic treatment is 185-200W.

[0016] Furthermore, the processing time of the microwave-ultrasound coordinated processing is 45 to 90 seconds.

[0017] Furthermore, the step of obtaining a lithium metatitanate precursor includes the following process:

[0018] Adding a titanium source and a lithium source into a second solvent, stirring and mixing, and then drying, grinding and sintering to obtain the lithium metatitanate precursor;

[0019] The molar ratio of Ti in the titanium source to Li in the lithium source is 1:(2-2.2); the sintering working condition parameters include: temperature of 750-800° C. and time of 12-16 hours.

[0020] Furthermore, the titanium source includes at least one of titanium dioxide and metatitanic acid; the lithium source includes at least one of lithium carbonate, lithium hydroxide and lithium chloride; and the second solvent includes water.

[0021] Furthermore, the weight ratio of the lithium metatitanate precursor, the adhesive forming agent, the pore-forming agent and the first solvent is (68-75):(15-20):(5-10):(100-109);

[0022] The adhesive forming agent comprises at least one of polyvinyl butyral, polyvinyl pyrrolidone, polyvinyl chloride, chlorinated polyvinyl chloride, polyacrylic acid, polyacrylonitrile, polyacrylamide, polymethyl methacrylate, polystyrene, polyamide, polyimide, polyvinylidene fluoride, nitrile rubber, styrene-butadiene rubber, polyvinyl alcohol, polyethylene glycol, chitosan, polysulfone, polyetheretherketone, polytetrafluoroethylene and cellulose acetate butyrate;

[0023] The first solvent includes at least one of dichloromethane, chloroform, carbon tetrachloride, toluene, acetone, ethyl acetate, N,N-dimethylformamide, N-dimethylacetamide and N-methylpyrrolidone.

[0024] Furthermore, the adhesive forming agent is composed of polyvinyl butyral ester and polyvinyl pyrrolidone in a weight ratio of (3-6): (2-4); the pore-forming agent includes at least one of sodium carbonate and potassium carbonate.

[0025] Furthermore, the acidification step includes the following process: adding a hydrochloric acid solution with a molar concentration of 0.2-0.8 mol / L, and then acidifying at a temperature of 40-50° C. for 10-20 hours.

[0026] In a second aspect, the present invention provides a titanium-based particle adsorbent, wherein the titanium-based particle adsorbent is prepared by the preparation method described in any one of the first aspects.

[0027] The above technical solution provided by the embodiment of the present invention has at least the following advantages compared with the prior art:

[0028] The embodiment of the present invention provides a titanium-based particle adsorbent and a preparation method thereof. Based on the existing titanium-based particle adsorbent preparation process, the present invention utilizes the synergistic effect of a microwave-ultrasonic composite field. When microwaves and ultrasonic waves under the above-mentioned specific parameter conditions in the present invention are simultaneously applied to system materials, the uniform heating and internal heating mechanism provided by the microwaves can accelerate the cavitation and mechanical stirring effects generated by the ultrasonic waves. At the same time, the dispersion and mixing effects of the ultrasonic waves can promote the heating and non-thermal effects of the microwaves, thereby improving the stability of the obtained titanium-based particle adsorbent, making it have excellent anti-dissolution performance and meeting the needs of multiple cycles in practical applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.

[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0031] Figure 1 A schematic flow chart of a method for preparing a titanium-based particle adsorbent provided in an embodiment of the present invention.

[0032] Figure 2 This is a product appearance diagram of the titanium-based particle adsorbent provided in Example 1 of the present invention. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0035] In a first aspect, the present invention provides a method for preparing a titanium-based particle adsorbent, such as Figure 1 As shown, the preparation method of the titanium-based particle adsorbent comprises the following steps:

[0036] Obtaining a lithium metatitanate precursor;

[0037] Adding the lithium metatitanate precursor, the adhesive forming agent and the pore-forming agent into a first solvent and stirring and mixing them to obtain a first mixture;

[0038] placing the first mixed material in a microwave-ultrasonic composite field for microwave-ultrasonic synergistic treatment to obtain a second mixed material;

[0039] Granulating the second mixed material, and then acidifying, filtering and drying to obtain the titanium-based particle adsorbent;

[0040] The working condition parameters of the microwave-ultrasound synergistic treatment include: ultrasonic power of 1500-1800W, and microwave power of 150-220W.

[0041] An embodiment of the present invention provides a method for preparing a titanium-based particle adsorbent. Based on the existing titanium-based particle adsorbent preparation process, the present invention utilizes the synergistic effect of a microwave-ultrasonic composite field. When microwaves and ultrasonic waves under the above-mentioned specific parameter conditions in the present invention are simultaneously applied to system materials, the uniform heating and internal heating mechanism provided by the microwaves can accelerate the cavitation and mechanical stirring effects generated by the ultrasonic waves. At the same time, the dispersion and mixing effects of the ultrasonic waves can promote the heating and non-thermal effects of the microwaves, thereby improving the stability of the obtained titanium-based particle adsorbent, making it have excellent anti-dissolution performance and meeting the needs of multiple cycles in practical applications.

[0042] In some specific embodiments, the "microwave-ultrasonic composite field" in the present invention can be directly carried out using existing ultrasonic microwave coupling equipment, such as the XO-SM series ultrasonic microwave combined reaction system, ultrasonic microwave reactor, etc.

[0043] In some specific embodiments, the ultrasonic power of the microwave-ultrasonic synergistic treatment is 1720-1750W.

[0044] In some specific embodiments, the microwave power of the microwave-ultrasound synergistic treatment is 185-200W.

[0045] In some specific embodiments, the microwave-ultrasound synergistic treatment takes 45 to 90 seconds.

[0046] In some specific embodiments, the step of obtaining a lithium metatitanate precursor includes the following process:

[0047] Adding a titanium source and a lithium source into a second solvent, stirring and mixing, and then drying, grinding and sintering to obtain the lithium metatitanate precursor;

[0048] The molar ratio of Ti in the titanium source to Li in the lithium source is 1:(2-2.2); the sintering working condition parameters include: temperature of 750-800° C. and time of 12-16 hours.

[0049] In some specific embodiments, the titanium source includes at least one of titanium dioxide and metatitanic acid; the lithium source includes at least one of lithium carbonate, lithium hydroxide and lithium chloride; and the second solvent includes water.

[0050] In some specific embodiments, the weight ratio of the lithium metatitanate precursor, the adhesive forming agent, the pore-forming agent and the first solvent is (68-75):(15-20):(5-10):(100-109);

[0051] The adhesive forming agent comprises at least one of polyvinyl butyral, polyvinyl pyrrolidone, polyvinyl chloride, chlorinated polyvinyl chloride, polyacrylic acid, polyacrylonitrile, polyacrylamide, polymethyl methacrylate, polystyrene, polyamide, polyimide, polyvinylidene fluoride, nitrile rubber, styrene-butadiene rubber, polyvinyl alcohol, polyethylene glycol, chitosan, polysulfone, polyetheretherketone, polytetrafluoroethylene and cellulose acetate butyrate;

[0052] The first solvent includes at least one of dichloromethane, chloroform, carbon tetrachloride, toluene, acetone, ethyl acetate, N,N-dimethylformamide, N-dimethylacetamide and N-methylpyrrolidone.

[0053] In some specific embodiments, the adhesive forming agent is composed of polyvinyl butyral ester and polyvinyl pyrrolidone in a weight ratio of (3-6):(2-4); the pore-forming agent includes at least one of sodium carbonate and potassium carbonate.

[0054] In some specific embodiments, the acidification step includes the following process: adding a hydrochloric acid solution with a molar concentration of 0.2-0.8 mol / L, and then acidifying at a temperature of 40-50° C. for 10-20 hours.

[0055] In a second aspect, based on the same concept, the present invention provides a titanium-based particle adsorbent, wherein the titanium-based particle adsorbent is prepared by the preparation method described in any one of the first aspects.

[0056] The titanium-based particle adsorbent provided by the present invention is realized based on the preparation method described in any one of the first aspects. Therefore, the titanium-based particle adsorbent has at least the beneficial effects of the technical solution described in any one of the first aspects, which will not be described in detail here.

[0057] It should be noted that the component raw materials involved in the titanium-based particulate adsorbent and the preparation method thereof provided in the embodiments of the present invention, unless otherwise specified or specified, can be directly commercially available products or homemade using existing public preparation methods; at the same time, the steps and parameters involved, unless otherwise specified or specified, can be carried out according to the existing processing technology of titanium-based particulate adsorbents or directly using existing equipment, and the present invention document will not describe them one by one.

[0058] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are intended only to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.

[0059] Example 1

[0060] This example provides a titanium-based particle adsorbent, and the preparation method of the titanium-based particle adsorbent comprises the following steps:

[0061] Step (1): adding a titanium source (specifically titanic acid) and a lithium source (specifically lithium hydroxide) into water and stirring and mixing, then placing in a 75°C environment for vacuum drying and grinding, and sintering the resulting mixture to obtain the lithium titanate precursor; wherein the molar ratio of Ti in the titanium source to Li in the lithium source is 1:2.05; and the sintering working condition parameters include: temperature of 780°C and time of 14 hours;

[0062] Step (2): adding the lithium metatitanate precursor, the adhesive forming agent and the pore-forming agent obtained in step (1) into N,N-dimethylformamide and stirring and mixing them to obtain a first mixture; wherein the weight ratio of the lithium metatitanate precursor, the adhesive forming agent, the pore-forming agent and the N,N-dimethylformamide is 72:18:7:105; the adhesive forming agent is composed of polyvinyl butyral ester and polyvinyl pyrrolidone in a weight ratio of 5:3; and the pore-forming agent is sodium carbonate;

[0063] Step (3): placing the first mixed material obtained in step (2) in a microwave-ultrasonic composite field for microwave-ultrasonic synergistic treatment to obtain a second mixed material; wherein the working condition parameters of the microwave-ultrasonic synergistic treatment include: ultrasonic power of 1735 W, microwave power of 190 W, and treatment time of 60 s;

[0064] Step (4): The second mixed material obtained in step (3) is extruded into clean water to form spherical particles, and spherical particles with a particle size of 2 to 3 mm are obtained. The spherical particles are then immersed in a hydrochloric acid solution with a molar concentration of 0.3 mol / L, and acidified at a temperature of 48°C for 15 hours. The mixture is filtered, washed with pure water and dried to obtain the titanium-based particle adsorbent.

[0065] Example 2

[0066] This example provides a titanium-based particle adsorbent, and the preparation method of the titanium-based particle adsorbent comprises the following steps:

[0067] Step (1): adding a titanium source (specifically titanic acid) and a lithium source (specifically lithium hydroxide) into water and stirring and mixing, then placing in a 75°C environment for vacuum drying and grinding, and sintering the resulting mixture to obtain the lithium titanate precursor; wherein the molar ratio of Ti in the titanium source to Li in the lithium source is 1:2.05; and the sintering working condition parameters include: temperature of 750°C and time of 16 hours;

[0068] Step (2): adding the lithium metatitanate precursor, the adhesive forming agent and the pore-forming agent obtained in step (1) into N,N-dimethylformamide and stirring and mixing them to obtain a first mixture; wherein the weight ratio of the lithium metatitanate precursor, the adhesive forming agent, the pore-forming agent and the N,N-dimethylformamide is 68:15:5:100; the adhesive forming agent is composed of polyvinyl butyral ester and polyvinyl pyrrolidone in a weight ratio of 5:3; and the pore-forming agent is sodium carbonate;

[0069] Step (3): placing the first mixed material obtained in step (2) in a microwave-ultrasonic composite field for microwave-ultrasonic synergistic treatment to obtain a second mixed material; wherein the working condition parameters of the microwave-ultrasonic synergistic treatment include: ultrasonic power of 1500 W, microwave power of 220 W, and treatment time of 45 s;

[0070] Step (4): The second mixed material obtained in step (3) is extruded into clean water to form spherical particles, and spherical particles with a particle size of 2 to 3 mm are obtained. The spherical particles are then immersed in a hydrochloric acid solution with a molar concentration of 0.3 mol / L, and acidified at a temperature of 48°C for 15 hours. The mixture is filtered, washed with pure water and dried to obtain the titanium-based particle adsorbent.

[0071] Example 3

[0072] This example provides a titanium-based particle adsorbent, and the preparation method of the titanium-based particle adsorbent comprises the following steps:

[0073] Step (1): adding a titanium source (specifically titanic acid) and a lithium source (specifically lithium hydroxide) into water and stirring and mixing, then placing in a 75°C environment for vacuum drying and grinding, and sintering the resulting mixture to obtain the lithium titanate precursor; wherein the molar ratio of Ti in the titanium source to Li in the lithium source is 1:2.05; and the sintering working condition parameters include: temperature of 800°C and time of 12 hours;

[0074] Step (2): adding the lithium metatitanate precursor, the adhesive forming agent and the pore-forming agent obtained in step (1) into N,N-dimethylformamide and stirring and mixing them to obtain a first mixture; wherein the weight ratio of the lithium metatitanate precursor, the adhesive forming agent, the pore-forming agent and the N,N-dimethylformamide is 75:20:10:109; the adhesive forming agent is composed of polyvinyl butyral ester and polyvinyl pyrrolidone in a weight ratio of 5:3; and the pore-forming agent is sodium carbonate;

[0075] Step (3): placing the first mixed material obtained in step (2) in a microwave-ultrasonic composite field for microwave-ultrasonic synergistic treatment to obtain a second mixed material; wherein the working condition parameters of the microwave-ultrasonic synergistic treatment include: ultrasonic power of 1800 W, microwave power of 150 W, and treatment time of 90 s;

[0076] Step (4): The second mixed material obtained in step (3) is extruded into clean water to form spherical particles, and spherical particles with a particle size of 2 to 3 mm are obtained. The spherical particles are then immersed in a hydrochloric acid solution with a molar concentration of 0.3 mol / L, and acidified at a temperature of 48°C for 15 hours. The mixture is filtered, washed with pure water and dried to obtain the titanium-based particle adsorbent.

[0077] Comparative Example 1

[0078] This example provides a titanium-based particulate adsorbent and a preparation method thereof, which differs from Example 1 only in that the microwave-ultrasonic synergistic treatment in step (3) is adjusted to ultrasonic treatment; the remaining steps and parameters are the same.

[0079] The preparation method of the titanium-based particle adsorbent comprises the following steps:

[0080] Step (1): adding a titanium source (specifically titanic acid) and a lithium source (specifically lithium hydroxide) into water and stirring and mixing, then placing in a 75°C environment for vacuum drying and grinding, and sintering the resulting mixture to obtain the lithium titanate precursor; wherein the molar ratio of Ti in the titanium source to Li in the lithium source is 1:2.05; and the sintering working condition parameters include: temperature of 780°C and time of 14 hours;

[0081] Step (2): adding the lithium metatitanate precursor, the adhesive forming agent and the pore-forming agent obtained in step (1) into N,N-dimethylformamide and stirring and mixing them to obtain a first mixture; wherein the weight ratio of the lithium metatitanate precursor, the adhesive forming agent, the pore-forming agent and the N,N-dimethylformamide is 72:18:7:105; the adhesive forming agent is composed of polyvinyl butyral ester and polyvinyl pyrrolidone in a weight ratio of 5:3; and the pore-forming agent is sodium carbonate;

[0082] Step (3): placing the first mixed material obtained in step (2) in an ultrasonic device for ultrasonic treatment to obtain a second mixed material; wherein the working condition parameters of the ultrasonic treatment include: ultrasonic power of 1735W, and treatment time of 60s;

[0083] Step (4): The second mixed material obtained in step (3) is extruded into clean water to form spherical particles, and spherical particles with a particle size of 2 to 3 mm are obtained. The spherical particles are then immersed in a hydrochloric acid solution with a molar concentration of 0.3 mol / L, and acidified at a temperature of 48°C for 15 hours. The mixture is filtered, washed with pure water and dried to obtain the titanium-based particle adsorbent.

[0084] Comparative Example 2

[0085] This example provides a titanium-based particulate adsorbent and a preparation method thereof, which differs from Example 1 only in that the microwave-ultrasound synergistic treatment in step (3) is adjusted to microwave treatment; the remaining steps and parameters are the same.

[0086] The preparation method of the titanium-based particle adsorbent comprises the following steps:

[0087] Step (1): adding a titanium source (specifically titanic acid) and a lithium source (specifically lithium hydroxide) into water and stirring and mixing, then placing in a 75°C environment for vacuum drying and grinding, and sintering the resulting mixture to obtain the lithium titanate precursor; wherein the molar ratio of Ti in the titanium source to Li in the lithium source is 1:2.05; and the sintering working condition parameters include: temperature of 780°C and time of 14 hours;

[0088] Step (2): adding the lithium metatitanate precursor, the adhesive forming agent and the pore-forming agent obtained in step (1) into N,N-dimethylformamide and stirring and mixing them to obtain a first mixture; wherein the weight ratio of the lithium metatitanate precursor, the adhesive forming agent, the pore-forming agent and the N,N-dimethylformamide is 72:18:7:105; the adhesive forming agent is composed of polyvinyl butyral ester and polyvinyl pyrrolidone in a weight ratio of 5:3; and the pore-forming agent is sodium carbonate;

[0089] Step (3): placing the first mixed material obtained in step (2) in a microwave device for microwave treatment to obtain a second mixed material; wherein the working condition parameters of the microwave treatment include: microwave power of 190 W, treatment time of 60 s;

[0090] Step (4): The second mixed material obtained in step (3) is extruded into clean water to form spherical particles, and spherical particles with a particle size of 2 to 3 mm are obtained. The spherical particles are then immersed in a hydrochloric acid solution with a molar concentration of 0.3 mol / L, and acidified at a temperature of 48°C for 15 hours. The mixture is filtered, washed with pure water and dried to obtain the titanium-based particle adsorbent.

[0091] Comparative Example 3

[0092] This example provides a titanium-based particulate adsorbent and a preparation method thereof, which differs from Example 1 only in that the ultrasonic power of the microwave-ultrasonic synergistic treatment in step (3) is adjusted to 1200 W, and the microwave power is adjusted to 725 W; the remaining steps and parameters are the same.

[0093] The preparation method of the titanium-based particle adsorbent comprises the following steps:

[0094] Step (1): adding a titanium source (specifically titanic acid) and a lithium source (specifically lithium hydroxide) into water and stirring and mixing, then placing in a 75°C environment for vacuum drying and grinding, and sintering the resulting mixture to obtain the lithium titanate precursor; wherein the molar ratio of Ti in the titanium source to Li in the lithium source is 1:2.05; and the sintering working condition parameters include: temperature of 780°C and time of 14 hours;

[0095] Step (2): adding the lithium metatitanate precursor, the adhesive forming agent and the pore-forming agent obtained in step (1) into N,N-dimethylformamide and stirring and mixing them to obtain a first mixture; wherein the weight ratio of the lithium metatitanate precursor, the adhesive forming agent, the pore-forming agent and the N,N-dimethylformamide is 72:18:7:105; the adhesive forming agent is composed of polyvinyl butyral ester and polyvinyl pyrrolidone in a weight ratio of 5:3; and the pore-forming agent is sodium carbonate;

[0096] Step (3): placing the first mixed material obtained in step (2) in a microwave-ultrasonic composite field for microwave-ultrasonic synergistic treatment to obtain a second mixed material; wherein the working condition parameters of the microwave-ultrasonic synergistic treatment include: ultrasonic power of 1200 W, microwave power of 725 W, and treatment time of 60 s;

[0097] Step (4): The second mixed material obtained in step (3) is extruded into clean water to form spherical particles, and spherical particles with a particle size of 2 to 3 mm are obtained. The spherical particles are then immersed in a hydrochloric acid solution with a molar concentration of 0.3 mol / L, and acidified at a temperature of 48°C for 15 hours. The mixture is filtered, washed with pure water and dried to obtain the titanium-based particle adsorbent.

[0098] Test Example 1

[0099] In this example, according to the existing detection method (the performance test method in CN 117899804 A), the titanium-based particle adsorbents obtained in the above Examples 1 to 3 and Comparative Examples 1 to 3 were subjected to cyclic adsorption and analytical performance tests. The number of cycles was 30, and the Ti dissolution rate (%) was calculated. The test results are shown in Table 1.

[0100] Table 1

[0101] Test samples Ti dissolution rate (%) Example 1 0.009 Example 2 0.024 Example 3 0.031 Comparative Example 1 0.678 Comparative Example 2 1.052 Comparative Example 3 0.396

[0102] As shown in Table 1, compared with Comparative Examples 1 to 3, the titanium-based particle adsorbent provided in the embodiment of the present invention still maintains a low Ti dissolution rate after 50 cycles of adsorption and analytical performance tests, and the Ti dissolution rate of Example 1 can reach 0.009%, which has excellent anti-dissolution performance. In addition, the titanium-based particle adsorbent provided in Examples 1 to 3 of the present invention has the advantages of excellent adsorption capacity performance (Li adsorption capacity ≥ 10.0 mg / g), regular morphology, high molding rate, etc. The actual product appearance is shown in the figure. Figure 2 As shown, it can meet the needs of multiple cycles in practical applications.

[0103] In summary, the embodiments of the present invention provide a titanium-based particulate adsorbent and a preparation method thereof. Based on the existing titanium-based particulate adsorbent preparation process, the present invention utilizes the synergistic effect of a microwave-ultrasonic composite field. When microwaves and ultrasonic waves under the above-mentioned specific parameter conditions in the present invention are simultaneously applied to the system materials, the uniform heating and internal heating mechanism provided by the microwaves can accelerate the cavitation and mechanical stirring effects generated by the ultrasonic waves. At the same time, the dispersion and mixing effects of the ultrasonic waves can promote the heating and non-thermal effects of the microwaves, thereby improving the stability of the obtained titanium-based particulate adsorbent, making it have excellent anti-dissolution performance and meeting the requirements of multiple cycles in practical applications.

[0104] Various embodiments of the present invention may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present invention; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0105] The foregoing is merely a specific embodiment of the present invention, which enables those skilled in the art to understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features claimed herein.

Claims

1. A method for preparing a titanium-based particle adsorbent, characterized in that: The preparation method of the titanium-based particle adsorbent comprises the following steps: Obtaining a lithium titanate precursor; Adding the lithium metatitanate precursor, the adhesive forming agent and the pore-forming agent into a first solvent and stirring and mixing them to obtain a first mixture; placing the first mixed material in a microwave-ultrasonic composite field for microwave-ultrasonic synergistic treatment to obtain a second mixed material; Granulating the second mixed material, and then acidifying, filtering and drying to obtain the titanium-based particle adsorbent; The working condition parameters of the microwave-ultrasound synergistic treatment include: ultrasonic power of 1500-1800W, and microwave power of 150-220W.

2. The method for preparing a titanium-based particle adsorbent according to claim 1, characterized in that: The ultrasonic power of the microwave-ultrasonic synergistic treatment is 1720-1750W.

3. The method for preparing a titanium-based particle adsorbent according to claim 1, characterized in that: The microwave power of the microwave-ultrasound synergistic treatment is 185-200W.

4. The method for preparing a titanium-based particle adsorbent according to claim 1, characterized in that: The processing time of the microwave-ultrasound coordinated processing is 45 to 90 seconds.

5. The method for preparing a titanium-based particle adsorbent according to claim 1, characterized in that: The step of obtaining a lithium metatitanate precursor comprises the following process: Adding a titanium source and a lithium source into a second solvent, stirring and mixing, and then drying, grinding and sintering to obtain the lithium metatitanate precursor; The molar ratio of Ti in the titanium source to Li in the lithium source is 1:(2-2.2); the sintering working condition parameters include: temperature of 750-800° C. and time of 12-16 hours.

6. The method for preparing a titanium-based particle adsorbent according to claim 5, characterized in that: The titanium source includes at least one of titanium dioxide and metatitanic acid; the lithium source includes at least one of lithium carbonate, lithium hydroxide and lithium chloride; and the second solvent includes water.

7. The method for preparing a titanium-based particle adsorbent according to claim 1, characterized in that: The weight ratio of the lithium metatitanate precursor, the adhesive forming agent, the pore-forming agent and the first solvent is (68-75):(15-20):(5-10):(100-109); The adhesive forming agent comprises at least one of polyvinyl butyral, polyvinyl pyrrolidone, polyvinyl chloride, chlorinated polyvinyl chloride, polyacrylic acid, polyacrylonitrile, polyacrylamide, polymethyl methacrylate, polystyrene, polyamide, polyimide, polyvinylidene fluoride, nitrile rubber, styrene-butadiene rubber, polyvinyl alcohol, polyethylene glycol, chitosan, polysulfone, polyetheretherketone, polytetrafluoroethylene and cellulose acetate butyrate; The first solvent includes at least one of dichloromethane, chloroform, carbon tetrachloride, toluene, acetone, ethyl acetate, N,N-dimethylformamide, N-dimethylacetamide and N-methylpyrrolidone.

8. The method for preparing a titanium-based particle adsorbent according to claim 1, characterized in that: The adhesive forming agent is composed of polyvinyl butyral ester and polyvinyl pyrrolidone in a weight ratio of (3-6): (2-4); the pore-forming agent includes at least one of sodium carbonate and potassium carbonate.

9. The method for preparing a titanium-based particle adsorbent according to claim 1, characterized in that: The acidification step includes the following process: adding a hydrochloric acid solution with a molar concentration of 0.2-0.8 mol / L, and then acidifying at a temperature of 40-50° C. for 10-20 hours.

10. A titanium-based particle adsorbent, characterized in that: The titanium-based particle adsorbent is prepared by the preparation method described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for extracting steviol glycosides from stevia rebaudiana leaves

    CN106146574A

  • Method for preparing lithium ionic sieve adsorbent

    CN109012564A

  • Lithium adsorbent, preparation method and application thereof as well as method for extracting lithium from salt lake brine

    CN109759006A

  • Method for increasing specific surface area of coal series kaolin under synergistic effect of ultrasonic microwaves

    CN110844914A

  • Preparation method of titanium particle adsorbent with high adsorption stability

    CN116371373A

Cited By

  • High-temperature-resistant, high-adsorption and solution-loss-resistant titanium salt lake lithium extraction adsorbent and application thereof

    CN121003970A

  • High-temperature-resistant lithium-extraction adsorbent with high adsorption and anti-dissolution loss and use thereof

    CN121003970B